Immune cell dynamics and mechanisms of epithelial injury in celiac disease - Marafini, Irene; Salvatori, Silvia; Troncone, Edoardo; De Vico, Pasquale; De Cristofaro, Elena; Monteleone, Giovanni (Frontiers in Immunology, 2026)
Despite continuous exposure to dietary and microbial antigens, the intestinal mucosa maintains a delicate balance between immune activation and tolerance. This equilibrium depends on the integrity and regulatory functions of the intestinal epithelium and associated immune cells. In the case of celiac disease (CD), gluten ingestion disturbs this equilibrium in people with a genetic predisposition (those with HLA-DQ2 or HLA-DQ8 alleles), and this results in chronic inflammation and villous atrophy. Tissue transglutaminase 2 (TG2) modifies gluten peptides, thus enhancing their affinity for HLA-DQ2/8, with the downstream effect of triggering CD4+ T cell–mediated Th1 responses dominated by IFN-γ and IL-21. The same cytokines along with IL-15, which is released by the epithelial and dendritic cells, stimulate the activation of cytotoxic intraepithelial lymphocytes that, in turn, kill enterocytes. Additional innate pathways, including those induced by gliadin-derived peptides, α-amylase/trypsin inhibitors, and type I interferons, further amplify epithelial stress and immune activation. Crosstalk between immune and stromal cells and defects in counterregulatory mechanisms contribute to persistent tissue injury. Emerging evidence implicates the gut microbiota in modulating both gluten-dependent and -independent immune responses through protease activity and barrier regulation. We here review the available evidence supporting the role of immune cells in CD-associated tissue damage and discuss the basic mechanisms by which this destructive immune response is amplified.